Sistem Informasi Geografis Letak Puskesmas di Wilayah Kabupaten Tabanan Berbasis Web - I Komang Agus Ady Aryanto; Ni Made Ika Marini Mandenni (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
Technology is used as a tool in everyday life to accelerate the resolution of a problem one ofwhich is the design of Geographic Information Systems (GIS).The purpose of this study is tohelp collect and store data and analyze objects and geographical data to support decisionmaking in planning a mapping of the route search location to the nearest clinic that can helpthe community in Tabanan Regency. Using a Geographic Information System (GIS) allows itwill help the community in solving the problem of finding the location of the nearest clinicbecause in the presence of a GIS it will illustrate the location of the Clinic where the actualconditions are. The system built can display map data and data from the map can also bechanged dynamically. Here you will get a visualization of the location of the location in a webform so that it can be accessed anywhere and the information can be used as a reference fordecision makers, especially in the search for transportation routes that can be traversed to theclinic location is located. In addition, the information contained in the GeographicInformation System can be processed to provide a new discourse in the presentation ofgeographic information online that is equipped with data analysis in the form of images,descriptions and other attribute analysis. This research resulted in a program for Web-BasedGeographic Information System for Clinical Location Search in Tabanan Regency, which isable to display maps effectively with information. This process makes use of existing librarieson Google Maps combined with the Web Mapping process.